A gate-free MoS2 phototransistor assisted by ferroelectrics. (September 2019) - Wu, Shuaiqin; Wu, Guangjian; Wang, Xudong; Chen, Yan; Lin, Tie; Shen, Hong; Hu, Weida; Meng, Xiangjian; Wang, Jianlu; Chu, Junhao
Abstract: During the past decades, transition metal dichalcogenides (TMDs) have received special focus for their unique properties in photoelectric detection. As one important member of TMDs, MoS2 has been made into photodetector purely or combined with other materials, such as graphene, ionic liquid, and ferroelectric materials. Here, we report a gate-free MoS2 phototransistor combined with organic ferroelectric material poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)). In this device, the remnant polarization field in P(VDF-TrFE) is obtained from the piezoelectric force microscope (PFM) probe with a positive or negative bias, which can turn the dipoles from disorder to be the same direction. Then, the MoS2 channel can be maintained at an accumulated state with downward polarization field modulation and a depleted state with upward polarization field modulation. Moreover, the P(VDF-TrFE) segregates MoS2 from oxygen and water molecules around surroundings, which enables a cleaner surface state. As a photodetector, an ultra-low dark current of 10 –11 A, on/off ration of more than 10 4 and a fast photoresponse time of 120 μ s are achieved. This work provides a new method to make high-performance phototransistors assisted by the ferroelectric domain which can operate without a gate electrode and demonstrates great potential for ultra-low power consumption applications.